Structural basis of microRNA biogenesis by Dicer-1 and its partner protein Loqs-PB - Jouravleva, Karina; Golovenko, Dmitrij; Demo, Gabriel; Dutcher, Robert C; Hall, Traci M Tanaka; Zamore, Phillip D; Korostelev, Andrei A (Molecular cell, 2022)
In animals and plants, Dicer enzymes collaborate with double-stranded RNA-binding domain (dsRBD) proteins to convert precursor-microRNAs (pre-miRNAs) into miRNA duplexes. We report six cryo-EM structures of Drosophila Dicer-1 that show how Dicer-1 and its partner Loqs‑PB cooperate (1) before binding pre-miRNA, (2) after binding and in a catalytically competent state, (3) after nicking one arm of the pre-miRNA, and (4) following complete dicing and initial product release. Our reconstructions suggest that pre-miRNA binds a rare, open conformation of the Dicer‑1⋅Loqs‑PB heterodimer. The Dicer-1 dsRBD and three Loqs‑PB dsRBDs form a tight belt around the pre-miRNA, distorting the RNA helix to place the scissile phosphodiester bonds in the RNase III active sites. Pre-miRNA cleavage shifts the dsRBDs and partially closes Dicer-1, which may promote product release. Our data suggest a model for how the Dicer‑1⋅Loqs‑PB complex affects a complete cycle of pre-miRNA recognition, stepwise endonuclease cleavage, and product release.
Keywords: proteiny Drosophily; Loqs-PB; mikro RNA; Dcr-1; Dicer; dsRBD; Drosophila Proteins; RNA-Binding Proteins; Dicer-partner proteins; Loquacious; cryo-EM; MicroRNAs; miRNA; ribonukleasa III; Drosophila; isomiR; zvířata; proteiny vázající RNA; Ribonuclease III; RNase III; microRNA; Animals